ANALISIS KEBANGKRUTAN PERUSAHAAN SUB SEKTOR COAL MINING DI BURSA EFEK INDONESIA - Ayu Puspitaningtyas; Dhistianti Mei Rahmawan Tari (Jurnal Ekonomi dan Industri, 2021)
This study aims to determine the level of potential bankruptcy of a company. In this study, the company under study is coal mining sector listed on the IDX SMC Liquid. The companies include PT Adaro Energy Tbk (ADRO), PT Indika Energy Tbk(INDY), PT Indo Tambangraya Megah Tbk (ITMG) and PT Bukti Asam Tbk (PTBA). To research the company, researchers use 2 methods, namely the method of Altman and Grover and as a first step in knowing the bankruptcy signal of the company early. This type of research is descriptive quantitative. The data source used is secondary data. Population in this research is coal mining on IDX SMC Liquid issuer amounting to 4 coal mining company in period 2017-2020. The sample of research is using probability sampling method. The results of this study indicate that there are 2 methods used and generally have differences in the results of calculations, as well as publicly listed coal mining companies doesn’t have the potential to experience bankruptcy. Of the 2 methods used that are most accurate in determining the prediction of freedom is the Grover method.